Dehydration and rapid weight gain between weigh-in and competition in judo athletes: The differences between women and men - Ceylan, B.; Balci, S. S. (Research in Sports Medicine, 2023)
This study aimed to investigate the sex differences in short-term weight change and hydration status in judo athletes. Thirty-five men and 15 women judo athletes voluntarily participated in this descriptive and repeated measures design study. Body mass, urine-specific gravity (USG), and body composition of the athletes were measured at the official weigh-in and the competition day`s morning. Body mass of the athletes increased during recovery time between official weigh-in and before the competition (time factor; F1-48 = 71.81, p < 0.001), this increase was higher in men athletes compared to women athletes (time-sex interaction; F1-48 = 6.56, p = 0.01). With RWG, USG values of the women and men athletes decreased (time factor; F1-48 = 8.53, p = 0.005). However, most of the athletes were still in significant or serious dehydration state. Unchanged values of total body water rates (TBW) supported dehydration in athletes before the competition (time factor, F1-48 = 2.9, p = 0.091; time-sex interaction; F1-48= 2.4, p = 0.122). The findings of the study indicated that RWG was higher in men athletes compared to women athletes, but hydration status was not affected by sex factor.Notwithstanding 15 hours of recovery between official weigh-in and the start of the competition, judo athletes were still in dehydrated state despite remaining within the limit set for RWG.